Motivasi Guru dalam Prestasi Lomba Cipta Syair (Puisi) Siswa SD 1 Bakalan Krapyak Kudus - Adi Zainal Abidin; Nur Fajrie; Khamdun Khamdun (WASIS : Jurnal Ilmiah Pendidikan, 2023)
This research is a qualitative research with the aim of finding out the application of the learning process for writing poetry and the efforts made by the teacher to inspire kids' success in the primary school poetry competition for Elementary School 1 Students in the Bakalan Krapyak Kudus. This type of research is the use of a case study approach with a descriptive method. Collecting data in this study werw interviews, observations, and documentation of checking the validity of the data using, transferability, dependability, and confirmability. Data analisis tecniques used in this study data analysis Miles dan Huberman include data reduction, data presentation and drawing conclusions. The results of this study indicate that: poetry writing was established at SD 1 Bakalan Krapyak, Kudus Regency as an extracurricular activity to supplement curricular activities. The utilization of educational materials and assessments complements the teacher's personal approach to encouraging copyright competition success